High-performance natural fiber-reinforced cement composites - Hakamy, A.; Shaikh, Faiz; Low, I. (2018)
© 2018 Elsevier Ltd. All rights reserved. Cement nanocomposites reinforced with hemp fabrics and calcined nanoclay (CNC) have been fabricated and investigated. CNC is prepared by heating nanoclay (Cloisite 30B) at 900°C for 2h. The influences of CNC dispersion on the mechanical properties and thermal properties of these composites have been characterized in terms of porosity, density, water absorption, flexural strength, fracture toughness, durability impact strength, and thermal stability. The microstructure is investigated using quantitative X-ray diffraction analysis and high-resolution transmission electron microscopy. The effects of alkali (NaOH) treatment of hemp fabric on the mechanical properties of hemp fabric-reinforced cement composites with different fabric contents of 4.5, 5.7, 6.9, and 8.1 wt% are also investigated. Results show that the optimum hemp fabric content is 6.9 wt% (i.e., six fabric layers). Results also indicated that physical, mechanical, and thermal properties enhanced because of the addition of CNC into the cement matrix and the optimum content of CNC was 1 wt%. The treated hemp fabric-reinforced nanocomposites containing 1 wt% CNC exhibited the highest flexural strength, fracture toughness, impact strength, and thermal stability than their counterparts and good fiber-matrix interface. Results also indicated that the CNC effectively mitigated the degradation of hemp fiber. The durability and the degradation resistance of hemp fiber were enhanced due to the addition of CNC into the cement matrix and the optimum content of CNC was 1 wt%. This environmentally friendly nanocomposite can be used for various construction applications such as ceilings and roofs.